Paracremonium yunnanense (Sordariomycetes), a New Fungus From Swallow Cave in Yunnan Province, China - Xiang‐Fu Liu; Saowaluck Tibpromma; Kevin D. Hyde; Jayarama D. Bhat; Dong‐Qin Dai; Abdallah M. Elgorban; K. W. Thilini Chethana; Samantha C. Karunarathna (New Zealand Journal of Botany, 2026)
In this article, we describe a new cave‐associated fungus belonging to Nectriaceae (Hypocreales), collected from the air in Swallow Cave, Yunnan Province, China. Initial morphological observations confirmed that our collection exhibits characteristics typical of an acremonium‐like species. Phylogenetic analyses of the combined internal transcribed spacer (ITS), large subunit ribosomal RNA (LSU), and β‐tubulin ( TUB ) sequence dataset confirmed that our fungus forms an independent lineage within Paracremonium , sister to P. bendijkiorum , P. apiculatum , and P. variiforme . Based on morphology and multigene phylogeny, we describe our fungus as a new species, Paracremonium yunnanense . A comprehensive description, micrographs, and a phylogenetic tree showing the placement of the new species are provided. Moreover, our results contribute to understanding the genus Paracremonium and expand the knowledge of cave‐associated fungi in China.